Potensi Ekowisata Mangrove Batu Lumbang Sebagai Destinasi Wisata di Tahura Bali - Lumanauw, Nelsye; Benazira, Aulia (Politeknik Pariwisata Medan, 2023)
Batu Lumbang Mangrove Ecotourism boasts a variety of natural, cultural, and social potentials that can attract tourists. However, this potential isn't fully supported by the readiness of facilities and infrastructure. This research aims to uncover the potential of mangrove ecotourism as a tourist destination. The research employs a descriptive qualitative analysis method. Data collection, processing, and analysis were carried out based on the six components of tourism, attraction, accessibility, amenities, package, activities, and ancillary. In conclusion, this study underscores the potential of mangroves as a tourism destination. However, the identified obstacles through the 6A approach underline the need for comprehensive management efforts to enhance the area's infrastructure and facilities, in alignment with the principles of ecotourism and sustainable tourism. By effectively and sustainably managing tourism destinations, the local community stands to benefit.